Integrating Learning Development into the Student Experience - Pat Hill (Association for Learning Development in Higher Education (ALDinHE), 2013)
ÃÂ Ã¢â¬ËEmbedding skillsÃ¢â¬â¢ has become an educational buzz word which evokes many different responses. Whilst acknowledging this diversity, this article focuses on the promotion of the integration of skills development into the subject curriculum as theory is put into practice. A range of attitudes towards integrated learning development are discussed and there is an attempt to define the generic principles associated with integration. Different models of embedding are provided through case studies available on a new website developed as part of a University funded Teaching and Learning Project. The journey towards a more strategic level of integration though the course validation process is outlined along with ideas for continuing progress.